Manajemen Kurikulum Muatan Lokal Aswaja Dalam Membentuk Karakter Peserta Didik - Muhamad Fajriansyah (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2023)
This research aims to explain the management of the Aswaja local content curriculum. The Aswaja local content curriculum implemented follows the management steps known as the POAC (Planning, Organizing, Actuating, and Controlling) theory or principles. This study seeks to address issues regarding the curriculum management process from beginning to end. The data collection techniques in this study were conducted through three steps: observation, documentation, and interviews. The research results show that: 1) The planning of the Aswaja local content curriculum involves determining the subjects, appointing the teachers, identifying funding sources, and selecting learning resources; 2) The implementation of the curriculum includes reviewing the syllabus, creating lesson plans, and preparing assessments; 3) The evaluation of the curriculum involves evaluating the local content program and its outcomes. However, the strategy implemented by the head of the madrasah in the local content curriculum has not been fully effective, as there are frequent changes in teachers for local content subjects, and the teachers' abilities in designing and applying learning tools are still lacking. The head of the madrasah has not been innovative in developing the local content curriculum and the teaching methods applied, and the supervision of the implementation of the Aswaja local content curriculum has been insufficient.